Ultrasound-guided Percutaneous Dilatational Tracheotomy: A fast and safe technique for airway management: Preliminary Report of a Novel Technique: Ultrazvočno vodena perkutana dilatacijska traheotomija: hitra in varna tehnika oskrbe dihalne poti Preliminarno poročilo o novi tehniki - Metterlein, Thomas; Negele, Sabrina; Wunder, Christian; Roewer, Norbert; Schuster, Frank (Acta Medico-Biotechnica, 2021)
Purpose: To describe a modified technique for percutaneous dilational tracheotomy (PDT) offering possible significant advantages over currently used procedures.Methods: An observational animal study using ultrasound for PDT was performed. After pre-incisional ultrasonic examination, and with continuing ultrasound guidance, the trachea was punctured with an 18-gauge introducer needle and a tracheal tube was inserted using the Seldinger technique and a Ciaglia single dilator. Setting: University Hospital animal laboratory center. Subjects: 11 pietrain pigs (weight 26–36 kg).Results: Successful tracheotomy was accomplished in all 11 pigs. The mean duration of the procedure was 20 seconds from skin penetration to guide wire placement. In one pig, the dorsal wall of the trachea was punctured.Conclusion: This novel procedure is a simple and effective technique for PDT tube placement.
Keywords: percutaneous dilatational tracheotomy; ultrasound; animal study